SGS-LTER 1986 proposal - Shortgrass Steppe Long Term Ecological Research (SGS-LTER), author (Colorado State University. Libraries, 1986)
We propose to continue the long-term ecological research project in the Shortgrass Steppe, at the Central Plains Experimental Range in north central Colorado. The theme of this work revolves around the ideas of the origin and maintenance of spatial pattern in shortgrass ecosystems and the rules for transforming information about a particular temporal or spatial scale to information about the next higher scale in a hierarchy. The research we are proposing is organized by a nested hierarchy of spatial scales ranging from a single plant up to the Central Grassland region of the United States. The five LTER Core Topics provide a secondary organizing structure for the proposed work. Experiments are proposed for a range of spatial scales over each of the Core Topics. Our overall objective for this work is to begin unraveling some of the apparent complexities surrounding the issues of spatial and temporal heterogeneity and relationships among various scales of each. Even partial confirmation or rejection of these ideas will provide essential information to help move ecosystem ecology in the direction of principles for relating ecological processes and structures to spatial and temporal heterogeneity.
Long-term ecological research program: shortgrass steppe
Proposal submitted to National Science Foundation Ecosystems Studies Program, April 10, 1986; Principal investigator: W. K. Lauenroth; co-principal investigators: R. G. Woodmansee, A. R. Grable.
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Keywords: long term ecological research; Central Plains Experimental Range; Pawnee National Grassland; grassland ecology; shortgrass steppe